2003
DOI: 10.1034/j.1600-0536.2003.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of in vitro release of interferon‐γ in the diagnosis of contact allergy to potassium dichromate – a controlled study

Abstract: The use of in vitro release of interferon-gamma (IFN-gamma) in the diagnosis of contact allergy to potassium dichromate was studied in 20 patients who had positive patch tests to chromate and in 30 control subjects (10 patients with contact dermatitis, allergic to other allergens, 10 patients with other dermatologic diseases and 10 healthy subjects). The release of IFN-gamma in the supernatants of the peripheral blood lymphocytes was significantly higher in the patients with proven allergy to chromate (P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
(10 reference statements)
1
14
0
1
Order By: Relevance
“…Moreover, release of cytokines could only be detected in half of the MCI‐allergic patients. Regarding the metal chromate, lymphocyte proliferation responses could be detected in approximately 70% of chromate‐allergic patients (14–16). For fragrances, Sieben et al (17) found no or only very infrequent fragrance‐specific T‐cell responses, with only 31% of patch test‐positive patients having a positive T‐cell response.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, release of cytokines could only be detected in half of the MCI‐allergic patients. Regarding the metal chromate, lymphocyte proliferation responses could be detected in approximately 70% of chromate‐allergic patients (14–16). For fragrances, Sieben et al (17) found no or only very infrequent fragrance‐specific T‐cell responses, with only 31% of patch test‐positive patients having a positive T‐cell response.…”
Section: Introductionmentioning
confidence: 99%
“…Van den Broeke et al [19] reported a Th1 cytokine profile in patients allergic to nickel, and a previous study by our group of IFN-γ expression in peripheral blood mononuclear cells (PBMCs) of 20 patients with patch-proven allergy to potassium dichromate yielded significantly higher levels in the patients than in controls [8] . However, later studies suggested a role for Th2 cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte transformation and macrophage migration inhibition have been evaluated as measures of ACD in animals and humans [6,7] but have not yet gained widespread acceptance in clinical practice. Previously, using an ELI-SA technique, we demonstrated that lymphocytes from peripheral blood of individuals with chromate allergy produced significantly higher amounts of interferon (IFN)-γ in response to chrome stimulation than lymphocytes from nonallergic individuals [8] .…”
mentioning
confidence: 99%
“…These researchers performed 24-hour cultures stimulated with potassium dichromate and phytohemagglutinin, a non-specific activator of T cells supposedly used to initiate and expand the reaction. 17,18 …”
Section: Discussionmentioning
confidence: 99%